Morphometric analysis of three normal facial types in mixed dentition using posteroanterior cephalometric radiographs: preliminary results - Bigliazzi, Renato; Walverde, Eliana Ayala; Oliveira, Derly Tescaro Narciso de; Bertoz, André Pinheiro de Magalhães; Faltin Junior, Kurt (Acta Scientiarum. Health Sciences, 2017)
The aim of the present investigation was to evaluate the craniofacial features of subjects with normal occlusion with different vertical patterns in the mixed dentition using morphometric analysis (Thin-Plate Spline analysis - TPS) applied to posteroanterior (PA) films. The sample comprised 39 individuals (18 females and 21 males), all in mixed dentition, aged from 8.4 to 10 years with satisfactory occlusion and balanced profile and with no history of orthodontic or facial orthopedic treatment. The sample was divided into three groups (mesofacial, brachyfacial and dolichofacial) according to the facial types proposed by Ricketts (1989). The average craniofacial configurations of each study group were obtained by orthogonal superimposition of Procrustes, thereby eliminating size differences and allowing only shape differences between groups to be analyzed by viewing the TPS deformation grid. Significant differences were found among the three facial types but were more remarkable between mesofacials and dolichofacials than between mesofacials and brachyfacials. TPS morphometric analysis proved efficient for accurate visualization of transverse and vertical differences among facial types even before pubertal growth spurt. These differences cannot be easily detected by traditional posteroanterior cephalometry.